The mystery of the ice cold rose—Microbiome of an Arctic winter frost flower. Issue 1 (4th February 2023) - Thiele, Stefan; Vader, Anna; Øvreås, Lise
Abstract: Under very cold conditions, delicate ice‐crystal structures called frost flowers emerge on the surface of newly formed sea ice. These understudied, ephemeral structures include saline brine, organic material, inorganic nutrients, and bacterial and archaeal communities in their brine channels. Hitherto, only a few frost flowers have been studied during spring and these have been reported to be dominated by Rhizobia or members of the SAR11 clade. Here we report on the microbiome of frost flowers sampled during the winter and polar night in the Barents Sea. There was a distinct difference in community profile between the extracted DNA and RNA, but both were dominated by members of the SAR11 clade (78% relative abundance and 41.5% relative activity). The data further suggested the abundance and activity of Cand . Nitrosopumilus, Nitrospinia, and Nitrosomonas . Combined with the inference of marker genes based on the 16S rRNA gene data, this indicates that sulfur and nitrogen cycling are likely the major metabolism in these ephemeral structures. Abstract : Here we report on the microbiome of frost flowers sampled during the winter and polar night in the Barents Sea. There was a distinct difference in community profile between the extracted DNA and RNA, but both were dominated by members of the SAR11 clade (78% relative abundance and 41.5% relative activity). The data further suggested high abundance and activity by Cand . Nitrosopumilus, Nitrospinia, and Nitrosomonas, indicating that sulfur and nitrogen cycling are likely the major metabolism in these ephemeral structures.